Analysis of the Application of Exceptio Non Adimpleti Contractus and Force Majeure as a Debtor's Defense in the Debt Payment Suspension Application Process (PKPU) - Hanim, Latifah; Wiranto, Agus Prasetia (UNISSULA Semarang, 2026)
This study analyzes the fundamental tension between the demands for procedural efficiency in the Suspension of Debt Payment Obligations (PKPU) process and the need for substantial justice in contract law, particularly regarding the application of debtor defenses in the form of Exceptio Non Adimpleti Contractus (ENAC) and Force Majeure. The background shows that PKPU, which is designed as a rescue mechanism, is often misused by creditors as an aggressive collection tool due to the strict interpretation of simple proof (Article 225 of the Bankruptcy Law) which hinders the examination of the creditor's default argument (ENAC) or force majeure. The research method used is normative law, applying a statutory and conceptual approach to the Bankruptcy Law and the Civil Code, with secondary data collection through literature studies and qualitative-deductive analysis. The results and discussion reveal that ENAC is difficult to accept because it requires substantial proof that goes beyond the limits of simple proof, while Force Majeure faces high resistance in money debt, even though its recognition can exempt the debtor from fines and interest. The conclusion suggests that the Commercial Court's failure to consider these material defenses risks transforming the PKPU into a collection instrument that threatens the continuity of fundamentally sound businesses. Suggestions include establishing more concrete prima facie evidence guidelines for material exceptions, synchronizing the debtor's substantive rights in the Civil Code, and encouraging businesses to specify Force Majeure clauses in their contracts.